2010
DOI: 10.1093/ndt/gfq450
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MMF efficacy and safety in paediatric vs. adult renal transplantation: subgroup analysis of the randomised, multicentre FDCC trial

Abstract: Both patient and allograft survival proved to be excellent in paediatric patients (98.4% and 90.3%) and adults (96.8% and 95.0%). The rates of biopsy-proven acute rejections (BPAR) and treated acute rejection episodes (ARE) were comparable between paediatric (12.9% and 17.7%) and adult patients (15.5% and 20.7%). Transplant function at 12 months post-transplant was similar in paediatric (67.8 ± 45.6 mL/min/1.73 m2;) and adult recipients (64.7 ± 23.3 mL/min/1.73 m2;). Children < 6 years (n = 10) exhibited a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…This observation is also consistent with data from clinical studies, which demonstrated comparable efficacy of MMF regarding the prevention of acute rejection episodes in paediatric renal transplant recipients [2,4]. Data from this and previous studies in paediatric [11] and adult renal transplant recipients [13] also show that IMPDH activity returns to baseline within 4-8 h of administration of MMF.…”
Section: Mpa Concentration (Mg/l) Impdh Inhibition (%)supporting
confidence: 89%
See 1 more Smart Citation
“…This observation is also consistent with data from clinical studies, which demonstrated comparable efficacy of MMF regarding the prevention of acute rejection episodes in paediatric renal transplant recipients [2,4]. Data from this and previous studies in paediatric [11] and adult renal transplant recipients [13] also show that IMPDH activity returns to baseline within 4-8 h of administration of MMF.…”
Section: Mpa Concentration (Mg/l) Impdh Inhibition (%)supporting
confidence: 89%
“…The overall efficacy and safety of MMF appear to be similar in paediatric and adult renal transplant recipients [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The recommended MMF dosage in conjunction with tacrolimus or without a concurrent CNI is 900 mg/m 2 per d in two divided doses (92); however, recent data indicate that the recommended MMF dosage of 1200 mg/m 2 per d in conjunction with CsA leads to MPA underexposure early after transplantation in approximately 60% of patients, indicating a need for a higher initial MMF dosage for optimal immunosuppressive activity (14). For achieving adequate MPA exposure in the majority of patients, an initial MMF dosage of 1800 mg/m 2 per d in conjunction with CsA and 1200 mg/m 2 per d in conjunction with tacrolimus for the first 2 to 4 weeks after transplantation has been suggested (14,93).…”
Section: Pediatric Transplantationmentioning
confidence: 99%
“…A limitation, however, was that trough‐level data were not available for all patients who relapsed, with one child who had the lowest AUC relapsing several times. In a recent RCT, which analysed paediatric data separately, it was demonstrated that ‘overall efficacy and tolerability of MMF in paediatrics appear to be comparable with that in adults’[39].…”
Section: Is Mycophenolate Used Off‐label Effective In Children?mentioning
confidence: 99%